Automated identification of elemental ions in macromolecular crystal structures. (1st April 2014) - Echols, Nathaniel; Morshed, Nader; Afonine, Pavel V.; McCoy, Airlie J.; Miller, Mitchell D.; Read, Randy J.; Richardson, Jane S.; Terwilliger, Thomas C.; Adams, Paul D.
<x xml:space="preserve">Abstract</x> Many macromolecular model‐building and refinement programs can automatically place solvent atoms in electron density at moderate‐to‐high resolution. This process frequently builds water molecules in place of elemental ions, the identification of which must be performed manually. The solvent‐picking algorithms in phenix.refine have been extended to build common ions based on an analysis of the chemical environment as well as physical properties such as occupancy, B factor and anomalous scattering. The method is most effective for heavier elements such as calcium and zinc, for which a majority of sites can be placed with few false positives in a diverse test set of structures. At atomic resolution, it is observed that it can also be possible to identify tightly bound sodium and magnesium ions. A number of challenges that contribute to the difficulty of completely automating the process of structure completion are discussed.